To the issue of functioning civil society and building legal state in Ukraine - Шевченко, Анатолій Євгенійович; Старостюк, Алла Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
This scientific article is dedicated to the theoretical and historical problems of the civil society and of the legal state the peculiarities of functioning on the current stage of development Ukraine.